Vertigo Perifer Et Causa Penyakit Meniere - Dinda Fitria; Ichwanuddin Ichwanuddin (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Vertigo is a sensation or sensation of movement from the body and surrounding environment that is described as a circular sensation, usually accompanied by complaints of nausea and vomiting, and balance disturbances. Vertigo is the third most common complaint by patients who come to general practice, after headaches, and strokes. A 31-year-old man came to the emergency room of Cut Meutia Hospital with complaints of dizziness since 5 days ago and disappeared. Patients also complained of nausea but were not accompanied by vomiting since complaints of dizziness appeared. Dizziness is felt by patients when looking at the surrounding environment and is not triggered by a change in head position. In addition, the patient also has a buzzing tingling tingling tingling along with spinning dizziness attacks. The patient's hearing begins to fade when the patient's ears ring and finally settle down. Based on anamnesis, physical examination and extenuation examination, the patient was treated with peripheral vertigo et causa meniere disease. Governance is carried out in the form of inf. RL 20 gtt/min, inj. Omeprazol 2x1, inj. Ondansetron 2x1 and oral in the form of betahistin 2x1 and hydrochlorothiazide 1x1.